Diversity and conservation of birds associated with an urban landscape in the southwest Brazilian Amazon - Moura, Aloysio Souza de; Candido, Edilson; Machado, Felipe Santana; Leite, Leandro Henrique; Mariano, Ravi Fernandes; Fontes, Marco Aurélio Leite (Revista Agrogeoambiental, 2023)
The Amazon presents an arc of deforestation which has expanded into natural areas and bird community studies in these areas are incipient for urban landscapes after transformation. Therefore, the bird community in an urban landscape in the southwest Amazonian region within an area in the arc of deforestation was investigated. The observations were performed through linear transects, during the wet and dry seasons of 2013. Records were obtained using binoculars and cameras. A total of 191 species of birds were recorded. The species accumulation curve was not reaching the asymptote, showing that new species can be recorded with a sampling effort increase. The community has low richness as a result of pressure on Amazonian environments and a high degree of anthropization. However, there is relevant composition, because nectarivores, insectivorous, carnivores, omnivores, and granivores were found in all environments, as well as endemic and threatened species.